Microvesicles from Human Immortalized Cell Lines of Endothelial Progenitor Cells and Mesenchymal Stem/Stromal Cells of Adipose Tissue Origin as Carriers of Bioactive Factors Facilitating Angiogenesis - Agnieszka Krawczenko; Aleksandra Bielawska-Pohl; Maria Paprocka; Honorata Kraskiewicz; Agnieszka Szyposzynska; Elżbieta Wojdat; Aleksandra Klimczak (Stem Cells International, 2020)
Endothelial progenitor cells (EPCs) and mesenchymal stem/stromal cells (MSCs) are associated with maintaining tissue homeostasis and tissue repair. Both types of cells contribute to tissue regeneration through the secretion of trophic factors (alone or in the form of microvesicles). This study investigated the isolation and biological properties of microvesicles (MVs) derived from human immortalized MSC line HATMSC1 of adipose tissue origin and EPC line. The human immortalized cell line derived from the adipose tissue of a patient with venous stasis was established in our laboratory using the hTERT and pSV402 plasmids. The human EPC line originating from cord blood (HEPC-CB.1) was established in our previous studies. Microvesicles were isolated through a sequence of centrifugations. Analysis of the protein content of both populations of microvesicles, using the Membrane-Based Antibody Array and Milliplex ELISA showed that isolated microvesicles transported growth factors and pro- and antiangiogenic factors. Analysis of the miRNA content of isolated microvesicles revealed the presence of proangiogenic miRNA (miR-126, miR-296, miR-378, and miR-210) and low expression of antiangiogenic miRNA (miR-221, miR-222, and miR-92a) using real-time RT-PCR with the TaqMan technique. The isolated microvesicles were assessed for their effect on the proliferation and proangiogenic properties of cells involved in tissue repair. It was shown that both HEPC-CB.1- and HATMSC1-derived microvesicles increased the proliferation of human endothelial cells of dermal origin and that this effect was dose-dependent. In contrast, microvesicles had a limited impact on the proliferation of fibroblasts and keratinocytes. Both types of microvesicles improved the proangiogenic properties of human dermal endothelial cells, and this effect was also dose-dependent, as shown in the Matrigel assay. These results confirm the hypothesis that microvesicles of HEPC-CB.1 and HATMSC1 origin carry proteins and miRNAs that support and facilitate angiogenic processes that are important for cutaneous tissue regeneration.